FAKTOR-FAKTOR YANG MEMPENGARUHI INTENTION TO USE LAYANAN E-GOVERNMENT DI INDONESIA - Delia Delavona (2022)
E-Government is a system of digital interaction between the government and the community. The application of e-government in public operations is considered capable of encouraging public aspirations, information disclosure, and public participation in the government administration system. However, there is still inequality and not optimal implementation of e-government services. This must be a concern for the government because if it is not handled, the public cannot get comprehensive information and services. This study attempts to bridge the gap by examining the factors influencing intentions in using e-government services in Indonesia. The purpose of this study is to test the effect of accessibility, usefulness, electronic word of mouth, ease of obtaining service through electronic word of mouth as a mediation variable. The sample in this study was 511 Indonesian citizens obtained from the distribution of questionnaires. The data obtained were analyzed using the PLS Structural Equation Model (SEM) version 3. The results showed that accessibility, usefulness, electronic word of mouth, and ease of obtaining service significantly influenced the intention in using e-government services and electronic word of mouth mediated the influence between usefulness and ease of obtaining service on intention in using e-government services.